2005
DOI: 10.1021/ja0529135
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin and Lipoic Acid Catalyze the Denitrosation of Low Molecular Weight and ProteinS-Nitrosothiols

Abstract: The nitrosation of cellular thiols has attracted much interest as a regulatory mechanism that mediates some of the pathophysiological effects of nitric oxide (NO). In cells, virtually all enzymes contain cysteine residues that can be subjected to S-nitrosation, whereby this process often acts as an activity switch. Nitrosation of biological thiols is believed to be mediated by N2O3, metal-nitrosyl complexes, and peroxynitrite. To date, however, enzymatic pathways for S-denitrosation of proteins have not been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
145
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(156 citation statements)
references
References 73 publications
9
145
0
2
Order By: Relevance
“…Future work is necessary to fully uncover the role of Trx in other transnitrosation reactions of biological significance. Trx is involved in the nitrosothiol content of endothelial cells (16) and HeLa cells (29), and thus we anticipate that Trx and related proteins such as protein disulfide isomerase (30-32) will mediate index. The data were fit to a two-state folding model (Kaleidagraph), and the ⌬G of folding in water (⌬G fold°) was calculated.…”
Section: Resultsmentioning
confidence: 99%
“…Future work is necessary to fully uncover the role of Trx in other transnitrosation reactions of biological significance. Trx is involved in the nitrosothiol content of endothelial cells (16) and HeLa cells (29), and thus we anticipate that Trx and related proteins such as protein disulfide isomerase (30-32) will mediate index. The data were fit to a two-state folding model (Kaleidagraph), and the ⌬G of folding in water (⌬G fold°) was calculated.…”
Section: Resultsmentioning
confidence: 99%
“…Denitrosylation of GSNO by human thioredoxins has been studied by both the Holmgren and Stoyanovsky laboratories. Holmgren's group has reported a homolytic breakdown of GSNO generating GSH and NO [27], while Stoyanovsky has proposed a heterolytic breakdown of GSNO producing GSH and nitroxyl (HNO) [28]. However both groups suggest that other cellular nitrosylated proteins may serve as substrates for the thioredoxin system.…”
Section: Discussionmentioning
confidence: 99%
“…The first involves S-nitrosoglutathione (GSNO) reductase (GSNOR) (32, 33), an NADH-dependent oxidoreductase that specifically breaks down GSNO (protein-SNOs are not direct substrates). Because GSH/GSNO and protein-SH/protein-SNOs are in equilibrium via rapid transnitrosation reactions (34), GSNOR lowers the levels of protein S-nitrosothiols (35, 36) reactive toward GSH, including those that are S-nitrosylated under conditions of SNO signaling (5, 36) and nitrosative stress (35).It has recently been demonstrated that the thioredoxins (Trx) constitute a second class of broad spectrum denitrosylase (6,37,38). Maintained Trx activity requires thioredoxin reductase (TrxR) (thioredoxin system), an NADPH-dependent selenoprotein.…”
mentioning
confidence: 99%
“…It has recently been demonstrated that the thioredoxins (Trx) constitute a second class of broad spectrum denitrosylase (6,37,38). Maintained Trx activity requires thioredoxin reductase (TrxR) (thioredoxin system), an NADPH-dependent selenoprotein.…”
mentioning
confidence: 99%